Chiral Resolution and Pharmacological Characterization of the Enantiomers of the Hsp90 Inhibitor 2‐Amino‐7‐[4‐fluoro‐2‐(3‐pyridyl)phenyl]‐4‐methyl‐7, 8‐dihydro‐6H‐quinazolin‐5‐one Oxime. Issue 7 (17th April 2014) - Amici, Raffaella; Bigogno, Chiara; Boggio, Roberto; Colombo, Andrea; Courtney, Stephen M.; Dal Zuffo, Roberto; Dondio, Giulio; Fusar, Fulvia; Gagliardi, Stefania; Minucci, Saverio; Molteni, Marco; Montalbetti, Christian A. G. N.; et al.
Abstract Heat‐shock protein 90 (Hsp90) is a molecular chaperone involved in the stabilization of key oncogenic signaling proteins, and therefore, inhibition of Hsp90 represents a new strategy in cancer therapy. 2‐Amino‐7‐[4‐fluoro‐2‐(3‐pyridyl)phenyl]‐4‐methyl‐7, 8‐dihydro‐6H‐quinazolin‐5‐one oxime is a racemic Hsp90 inhibitor that targets the N‐terminal adenosine triphosphatase site. We developed a method to resolve the enantiomers and evaluated their inhibitory activity on Hsp90 and the consequent antitumor effects. The (S) stereoisomer emerged as a potent Hsp90 inhibitor in biochemical and cellular assays. In addition, this enantiomer exhibited high oral bioavailability in mice and excellent antitumor activity in two different human cancer xenograft models.